Benthonic foraminiferal distributions and quantitative transfer functions for the northwest European continental margin - Sejrup, HP; Birks, HJB; Kristensen, DK; Madsen, H (ELSEVIER SCIENCE BV, 2004)
A database of benthonic foraminiferal data from 298 sediment surface-samples from the northwest European (Ireland to Svalbard) and Iceland margin has been compiled. Samples deeper than 500 m on the continental slope and shallower than 30 m in coastal areas are not included. Bottom-water temperatures at the sites range between -1 and 12.5 degreesC and salinity between 33.5 and 35.5parts per thousand. Detrended correspondence analyses of percentage values of 65 benthonic foraminifera taxa, from 260 of the samples show a strong, statistically significant relationship between modem foraminiferal assemblages and summer temperature and salinity. Utilising weighted averaging partial least square regression, transfer functions for summer bottom-water temperature (T-s) and salinity (S-s) have been developed. The transfer functions have relatively low root-mean-square errors of prediction (expressed as a percentage of the range of the modem environmental gradient sampled)-for T-s, 3.9%, and for S-s, 9.02%-compared to transfer functions developed for other proxies, which commonly range from 8% to 20%. The distributions of benthonic foraminifera species are dependent on other factors than salinity and temperature such as nutrients, substrate, turbidity, current regime, different biological factors, different depth-related factors, etc. The present analyses demonstrate that for this group as for most other groups, there is an overall, but not necessarily direct, relationship with distribution and abundance and temperature and salinity conditions. The transfer functions have been tested on a late glacial-Holocene data set and an Eemian-Early Weichselian data set from the eastern North Sea region. These experiments suggest that transfer functions on benthonic foraminifera can be a useful new tool in palaeoceanographic and palaeoenvironmental work along the European North Atlantic seaboard. (C) 2004 Elsevier B.V. All rights reserved.